Peran Pendidikan Agama Kristen dalam Mencegah Bunuh Diri pada Generasi Muda - Neti Saekoko; Hendrik A.E Lao (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Suicide is an act committed by individuals against themselves. This study aims to investigate the role of Christian Religious Education (CRE) in preventing suicide among young people. The method used is qualitative descriptive with a literature study approach, where data is collected through analysis and description of information from various sources, including books and journal articles. The results of the study show that CRE contributes to preventing suicide through the formation of identity and meaning in life. By emphasizing Christian values and biblical knowledge, CRE helps teenagers find meaning in life and strengthen their faith. Through engaging teaching methods, CRE empowers youth to appreciate themselves and face life's challenges with a positive attitude. Additionally, social community support integrated within CRE is vital for the mental health of adolescents, creating a safe and supportive environment. Mental health and spirituality are interrelated, with CRE playing a role in developing spiritual maturity and providing a strong moral foundation. Thus, young people can maintain their mental and spiritual health and find hope amid difficulties.